O acesso ao Benefício de Prestação Continuada no contexto de mudanças tecnológicas: uma análise no período de 2017-2024 - Oliveira, Andréia Vanessa de (Universidade Estadual de Ponta Grossa, 2025)
This research focuses on access to the Continuous Cash Benefit (BPC) between 2017 and 2024. It is justified by the importance of understanding how access to the BPC has evolved in the context of the use of Information and Communication Technologies (ICTs) as tools to modify service delivery practices and intensify State strategies toward workers and citizens who rely on public services. The hypothesis is that demand for the BPC has increased due to population aging and changes in the concept of disability. The research problem addresses the rising demand for the BPC and the increasing judicialization as a means of reversing administrative denials by the National Institute of Social Security (INSS), the digitalization of benefit applications, and the challenges faced by the program’s target population. The study analyzes changes in BPC access through digital channels such as Meu INSS, platforms, e- Government, and Digital Government— all of which have been reshaped by ICTs. The central research question is: Do digital channels and platforms ensure inclusive access for users? Have eligibility criteria become more stringent following regulatory changes to BPC access? The study covers the period from 2017 to 2024, justified by the launch of the Meu INSS portal and relevant social and legislative developments during that time. The general objective is to analyze access to the BPC in light of technological and social changes. Specific objectives include analyzing how social changes, such as aging and the expansion of the concept of disability, have contributed to growing demand; identifying how the adoption of new technologies has impacted the operationalization of the BPC through INSS digital channels; examining how the target audience accesses these digital platforms to apply for the benefit; investigating how digital platforms have affected service provision at Social Assistance Reference Centers (CRAS); and characterizing the context of increasing demand and judicialization based on court rulings from the 4th Federal Court of Ponta Grossa between January 2022 and August 2023. This is a qualitative, descriptive-exploratory study composed of bibliographic, documentary, and field research. Data collection involves semi-structured interviews with social workers from CRAS and INSS. The research seeks to understand access to the BPC from 2017 to 2024, the increase in demand due to population aging and changes in the disability concept, and the growing judicialization used to overturn administrative denials by the INSS. Findings indicate that BPC applicants experience digital exclusion, facing difficulties both in accessing information and in applying for the benefit through administrative channels—due to lack of access to devices or difficulty using them, reflecting the platformization of public services. Judicial rulings also reveal that INSS’s strict legal interpretation often disregards the social and economic realities faced by applicants, especially those in extreme vulnerability. Judicial analysis thus serves as a counterbalance to the productivity-oriented logic currently dominating the BPC system, reaffirming the importance of robust social and public policy.
Keywords: Benefício de Prestação Continuada; Tecnologia da Comunicação e da Informação; INSS Digital; Governo Digital; Assistência Social; Ciências Sociais Aplicadas